The implications of the COVID-19 pandemic on fairness and fair play for Olympic athletes training for the Tokyo Olympic Games - Schneider, A.; Hellal, M. (Philosophy, Sport, and the Pandemic, 2022)
The COVID-19 pandemic, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has led to detrimental changes in all aspects of life worldwide. As the sporting community continues to face various issues, including the postponement of the Tokyo Summer Olympic and Paralympic Games, the effects are being felt by all parties involved. In particular, there has been ongoing research investigating Olympic athletes and the unintended consequences they experience as a result of the pandemic. The repercussions are analyzed based on measures taken by nations and organizations, including the International Olympic Committee (IOC), and the effects these actions have on the health and well-being of athletes. This chapter seeks to examine the implications of the current COVID-19 pandemic on elite Olympic athletes and to identify the potential impact on fairness in general and fair play in sport at the Tokyo Games. Key emerging themes presented in the current literature include financial, physiological, psychological, and sociological concerns for athletes.